A Study of Consumer Behavior in Apparel Industry in Delhi (International Journal of Innovative Research in Engineering & Management, 2021)
India is now a rapidly growing country in terms of retails  business, on track to achieve a half-million million sales  locations by 2030. All of these factors are beneficial to Indian  textile businesses in the long term. However, the global  recession appears to be deteriorating with each day, as long as  countries such as those in South and Southeast Asia continue to  expand as well as thrive, fabric business will continue to thrive.  The research paper aimed to learn about the socio-economic  features of customers who prefer branded apparel and the  variables that impact their decision to purchase branded  apparel. Primary data were obtained from 200 customers using  a questionnaire throughout Delhi to satisfy the goals.  According to the findings of the survey, today's customers are  brand aware. They like branded apparel to seem more trendy,  and branded apparels also reflect an individual's prestige.  Consumers choose branded apparel because they are more  durable, has better diversity, and is of a high standard. Although  there has been an attempt to identify the quality of products, pricing characteristics, and promotional characteristics that are  engaged in planning, as well as whether that there's any  substantial association between demographic factors and  purchasing behavior.
Keywords: Apparels; Consumers; Fashion; Purchasing; Textile